Design of Reporting, Evaluation, and Monitoring Application for Student Organization Activity in University - Soesanto, Rayinda Pramuditya; Rizana, Afrin Fauzya; Andrawina, Luciana (International Journal of Innovation in Enterprise System, 2019)
In few decades, the development of information system has been increased rapidly. It is because most organization in various sector of industries, commerce, government, or even education become highly dependent on the use of the information system. This study aimed to design the application that will facilitate the activities in organization based on what user needs. The object of this study is student affair department in one of faculty in one of the universities in Indonesia. The method employed in this study to design the system is waterfall method. The system designed in this study is the focus for the activities related to student organization activities. The result of this study is there are eight dimensions quality that has to be fulfilled by the system according to the result of focus group discussion and Delphi method. The system designed in this study was adjusted to the needs that have been defined previously.